Amino-propyltriethoxysilane Modified Heavy Metal Sensor Based on Silicon Nanowire Arrays. (December 2018) - Ehfaed, Nuri. A.KH.; Bathmanathan, Shillan; Adam, Tijjani; Mohammed, Mohammed; Mohammed, Aeshah M.; Dahham, Omar S.; Hashim, U.; Noriman, Nik Z.
Abstract: Safety of consuming water from various resources can be questioned nowadays due to high content of material that is highly possible to have toxic content and cause permanent damage to human itself. Possible toxic content includes heavy metal such as lead, arsenic, cadmium and mercury. A highly sensitive or selective heavy metal sensor needed to aid in detection of these metal species. In this paper, the manipulation of silicon nanowire to detect heavy metal content in liquid sample is explained. Device is fabricated into two main elements which is the detecting part which is the nanowire and probes on the both sides. Next, the characterizations of the device are discussed as well as the discussion on the detections capabilities. The APTES surface modified integrated electrochemical nano-sensor was subjected to various concentration of lead ions, the responses were monitored assessed for the detection ion chemical activities, this response were observed using semiconductor parametric analyzer (SPA). The surface modified nano-sensor show a linear behavior with current response between 2-140pA, the detection limit for the lead ions was 0.1µm/l. The water samples which were collected in Taman Tasik Damam in Malaysia show similar characterization for area of around 20 square meters. Thus, the excellent and reliable behavior shown by this device, it can be adopted as detection device for various heavy metal detection in near future.